Importance of social competency development during business university studies - Lucie Depoo; Markéta Šnýdrová; Ivana Šnýdrová; Gabriela Ježková Petrů (DANUBE: Law, Economics and Social Issues Review, 2020)
Adequate level of social competencies after university graduation is necessary for today's competitive environment. This study aims to identify and present most important social competencies based on perceptions of students and graduates of case business university. The data were collected by questionnaire survey of graduates in 2017-2018. Two dimensional statistical methods were used to evaluate the results. Examination of graduates leads to identification of factors affecting preferences in higher education to fill expectation of current society and labor market. Specific factors impacting evaluation of business education and its development are discussed. The results show current approaches towards social competency development. Limit of the study is a narrow focus on one private business university. It may be taken as case study and a base for further research and benchmarking between universities.
Keywords: 330; Social Competencies; Management; Education; Evaluation; University; Assurance